Current challenges and novel treatment strategies in double hit lymphomas. (February 2016) - Anderson, Mary Ann; Tsui, Alpha; Wall, Meaghan; Huang, David C. S.; Roberts, Andrew W.
High-grade B-cell lymphomas with recurrent chromosomal break points have been termed 'double hit lymphoma' (DHL). The most commonly seen DHL is diffuse large B-cell lymphoma (DLBCL) with t(14;18) and t(8;14) or t(8;22) resulting in overexpression of BCL2 and MYC, respectively. The increased proliferation due to MYC overexpression, without the ability for an apoptotic brake as a result of BCL2 overexpression, results in 'the perfect storm of oncogenesis'. Thus this disease presents a number of diagnostic and therapeutic challenges for the hematologist. The first and foremost challenge is to recognize the DHL. As different morphological entities can be affected it is incumbent on pathologists and clinicians to maintain a high index of suspicion especially in disease that appears unusually aggressive or refractory to therapy. Diagnosis by fluorescence in situ hybridization (FISH) is a sensitive and specific method for detection of the disease but is time-consuming and expensive. While detection by immunohistochemistry (IHC) is sensitive and correlates with survival, standardized methods for this are not widely agreed upon. The second and equally important challenge in DHL is optimizing clinical outcome in a group of patients for whom the prognosis is widely regarded as poor. While improvements have been achieved by dose escalating standard chemotherapeutic regimens, many patients continue to do badly. Furthermore as a disease of aging many patients are unsuitable for dose-intensive chemotherapy regimens. There are now multiple novel targeted agents in various stages of clinical development that offer hope for better outcomes without undue toxicity. Among the most exciting of these developments include specific inhibitors of both BCL2 and MYC.